G35 Crohns disease: Initial treatment and outcomes at 12 months. (27th April 2016) - Gavin, J; Ashton, JJ; Heather, N; Marino, LV; Beattie, RM
Abstract : Introduction: Exclusive enteral nutrition (EEN) is the primary therapy for induction of remission and growth restoration in newly diagnosed children with Crohns Disease (CD). Patients who failed to go into clinical remission were offered steroids with partial enteral nutrition (PEN) alongside diet or steroids alone. The aim of this retrospective study was to investigate the effect of PEN/ steroids alone on growth outcome and relapse rate compared to EEN as induction therapy. Methods: Basic clinical data including anthropometry, Paris classification, treatment type and outcome were collected at diagnosis, post induction therapy, at 3 months and at 1 year for 78 patients diagnosed from 2012–14. Clinical remission was determined using a physician global assessment and blood biochemistry. Relapse was defined as a change in medication due to worsening symptoms. Data are presented as median values. Results: Age at diagnosis was 13 years (2–16 years), n = 62 (79%) were male. Patients received either EEN; n = 43;PEN; n = 16 or steroids alone; n = 19 as induction therapy. All groups had similar rates of clinical remission post induction therapy; 67% EEN, 75% PEN, 79% Steroids. There were no differences in relapse rates within 6 months; 30% EEN, 37% PEN, 47%. There was no difference between the mode of primary induction and disease location or those who went on to require biological therapy (infliximab or adalimumab) EEN, 20%; PEN, 35.7% and Steroids 26.3%. There were no differences in height-for-age-z-scores (HAZ) at 1 year for any treatment group. Body mass index z-scores (BMIZ) had significantly improved in EEN and PEN groups at 1 year (EEN p < 0.001; PEN p < 0.001). Conclusion: EEN and PEN primary induction treatments improved BMIZ. The EEN group displayed an improved HAZ at 1year. We do not demonstrate a superiority of any induction therapy on relapse rate.